Nilai-Nilai Spiritual dalam Upacara Tradisi Lopis Raksasa di Pekalongan - Maiyang Resmanti; Umu Hana Amini; ‘Ufairoh Shoofii Abiyyi; Divani Majidullah Syarief; Asep Yudha Wirajaya (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2021)
The giant lopis tradition ceremony in Pekalongan is the one of cultural events called syawalan which the event is interested by local and foreign people. The problem of this study is how lopis can attract wider community. This research is descriptive qualitative research with data collection techniques using observations, interviews, and literature reviews. The collected data are the fact of field collecting and information about spiritual values in Pekalongan giant lopis tradition. It during the process of making giant lopis which the makers are advised to purify themselves first, then the manufacturing process begins with reading basmalah, continued with selawat during making lopis, and ended with hamdalah. The spiritual values attached to lopis symbolize interreligious harmony, human relation with other relatives, and relationship with God. However, it in the process of cutting giant lopis are sincerity and a form of submission to God. Thus, it is the values that attract an attention of visitors both local and foreign, in addition to the large lopis shape.